Interpretation Of Character Symbolism In Poetry According To The Poets Perspective - Olivia Rosalind (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This study aims to analyze the interpretation of character symbolism in poetry based on the poet's perspective. Using text analysis methods, this study explores how poets use metaphorical figures in poetry to convey deep meaning. Data was collected from specially selected poems, and analyzed to reveal the poet's interpretation of the symbolism of the characters in their works. The findings from this research provide valuable insight into the poet's creative process in using metaphorical figures as a tool for artistic expression and understanding meaning in poetry.